LITERATURE REVIEW ON THE ROLE OF SHARIAH VENTURE CAPITAL IN SUPPORTING THE GROWTH OF SMES IN INDONESIA - Permata Sari, Indah; Hasibuan, Hafni Juniyanti; Rozalinda, Rozalinda; Alias, Norma; Bahar, Muchlis; Wira, Ahmad (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research aims: This study analyzes the role of Sharia venture capital in enhancing the growth, competitiveness, and sustainability of MSMEs in Indonesia, while mapping global trends, thematic clusters, challenges, and opportunities in Sharia-based venture financing. Design/Methodology/Approach: A Systematic Literature Review (SLR) using the PRISMA protocol is combined with bibliometric analysis through VOSviewer. Publications from 2020–2024 indexed in Scopus were screened with defined criteria, and keyword co-occurrence mapping was conducted to identify thematic structures and research directions. Research findings: Six thematic clusters emerged: financing mechanisms, macroeconomic dynamics, technological innovation, governance and risk, entrepreneurship, and global market integration. Sharia venture capital strengthens MSME financing access, innovation, and ethical economic development, though challenges persist in literacy, collaboration, and regulatory support. Theoretical Contribution/Originality: The study fills a literature gap by integrating Islamic ethical principles with modern venture financing and offering a conceptual understanding of Sharia risk-sharing models in MSME empowerment. Practitioners/Policy Implications: Findings highlight the need for stronger regulation, investor education, institutional collaboration, digital transformation, and MSME capacity building. Research Limitations/Implications: Limitations stem from reliance on secondary data and database scope. Future research should assess empirical impacts, digital Sharia VC models, and governance mechanisms.